Extra-articular Medial Impression Fracture of the Talus: A Previously Undescribed Injury. Issue 6 (December 2018) - Wijers, Olivier; Looijen, Rosa C.; Halm, Jens A.; Schepers, Tim
Background: Peripheral fractures of the talus are uncommon. Almost all the literature regarding talar fractures consists of central intra-articular fractures, whereas studies about peripheral talar fractures are lacking. The aim of this study is to increase awareness in diagnosing an unusual peripheral extra-articular medial impression fracture of the talus. Methods: This study includes a retrospective case series of patients with an extra-articular medial impression fracture of the talus. Patient characteristics, trauma mechanism, diagnostics, fracture characteristics, and treatment were reported. Results: Eight consecutive patients with an extra-articular medial impression fracture of the talus were identified. In 80%, the trauma mechanism was a supination or inversion injury of the ankle and foot. An X-ray was obtained in all patients; in 7 (88%) patients, a computed tomography scan was done, and an additional magnetic resonance imaging was done in 3 (38%) patients. In 4 patients (50%), the correct diagnosis was missed at first presentation. The delay between injury and diagnosis was 0 to 180 days (of 36 days on average). Conclusion: This is the first case series to describe patients with a peripheral extra-articular medial impression fracture of the talus. Good clinical examination and judicious use of diagnostic imaging are a necessity to find the talar impression fractures in a timely manner, and treatment can be started immediately. Levels of Evidence: Level V